Human Regulatory T Cells From Umbilical Cord Blood Display Increased Repertoire Diversity and Lineage Stability Relative to Adult Peripheral Blood - Motwani, Keshav; Peters, Leeana D.; Vliegen, Willem H.; El-sayed, Ahmed Gomaa; Seay, Howard R.; Lopez, M. Cecilia; Baker, Henry V.; Posgai, Amanda L.; Brusko, Maigan A.; Perry, Daniel J.; Bacher, Rhonda; Larkin, Joseph; et al. (Frontiers in Immunology, 2020)
The human T lymphocyte compartment is highly dynamic over the course of a lifetime. Of the many changes, perhaps most notable is the transition from a predominantly naïve T cell state at birth to the acquisition of antigen-experienced memory and effector subsets following environmental exposures. These phenotypic changes, including the induction of T cell exhaustion and senescence, have the potential to negatively impact efficacy of adoptive T cell therapies (ACT). When considering ACT with CD4+CD25+CD127-/lo regulatory T cells (Tregs) for the induction of immune tolerance, we previously reported ex vivo expanded umbilical cord blood (CB) Tregs remained more naïve, suppressed responder T cells equivalently, and exhibited a more diverse T cell receptor (TCR) repertoire compared to expanded adult peripheral blood (APB) Tregs. Herein, we hypothesized that upon further characterization, we would observe increased lineage heterogeneity and phenotypic diversity in APB Tregs that might negatively impact lineage stability, engraftment capacity, and the potential for Tregs to home to sites of tissue inflammation following ACT. We compared the phenotypic profiles of human Tregs isolated from CB versus the more traditional source, APB. We conducted analysis of fresh and ex vivo expanded Treg subsets at both the single cell (scRNA-seq and flow cytometry) and bulk (microarray and cytokine profiling) levels. Single cell transcriptional profiles of pre-expansion APB Tregs highlighted a cluster of cells that showed increased expression of genes associated with effector and pro-inflammatory phenotypes (CCL5, GZMK, BHLHE40, CXCR3, and LYAR) with low expression of Treg markers (FOXP3 and IKZF2). CB Tregs were more diverse in TCR repertoire and homogenous in phenotype, and contained fewer effector-like cells in contrast with APB Tregs. Interestingly, expression of canonical Treg markers, such as FOXP3, TIGIT and IKZF2, were increased in CB CD4+CD127+ conventional T cells (Tconv) compared to APB Tconv, post-expansion, implying perinatal T cells may adopt a default regulatory program. Collectively, these data identify multiple surface markers (CXCR3, CCL5, and NKG7) that could be depleted to improve purity and stability of APB Tregs, and support the use of expanded CB Tregs as a potentially optimal ACT modality for the treatment of autoimmune and inflammatory diseases.